Forward Momentum: A study On Harmonic Syntax - Andreia Vieira Martins (2022)
Western music structure embeds many levels of syntactic organization regulating musical time. In the specific case of harmony, syntax at the meso time scale can be understood as sequences of chords that tend to promote a feeling of going somewhere. Played backward, harmonic sequences have been referred to as having "an aimless, meandering quality that makes the sounds seem pointless" (Huron, 2016, p.171). However, no perceptual or empirical studies have assessed the level to which the degree of tending is imposed by different playing directionality (i.e.., forward and backward). Furthermore, outside of tonal music, for which many archetypal structures have been proposed in music theory, harmonic syntax becomes more elusive in dictating a sense of tending in the listeners. Based on these observations, this work raises a hypothesis for the tending of harmonic structures across different harmonic systems. We conducted an online listening test to assert perceptually the degree of tending perceived by listeners. The listening test included 16 chord sequences stimuli divided into two groups. The group difference is related to the directionality of playback as either forward or backward. Stimuli included tonal, atonal, and serial excerpts extracted from musical pieces, and chord sequences in 5- and 7-TET, derived from a computer-aided algorithmic method in the Fourier space. This method allows to visualize the hierarchical harmonic lexicon of pitch-class sets in 5- and 7-TET, and the chord sequences were derived with controlled directionality based on shared pitch and interval class content.